Remote sensing of tropospheric pollutants originating from 1997 forest fire in Southeast Asia - Hashim, M.; Kanniah, K. D.; Asmala, A.; Rasib, A. W. (ARSRIN, 2004)
The massive forest fire in Indonesia in 1997 affected the whole Asian region by transporting large quantity of smoke plume. Malaysia bore the brunt due to its proximity, wind direction and weather conditions. Therefore this study aims at using coarse spatial but high temporal resolution Advanced Very High Resolution Radiometer (AVHRR) data of NOAA-14 satellite to detect and subsequently map the five primary fire pollutants i.e. carbon monoxide (CO), sulfur dioxide (SO2), nirogen dioxide (NO2), ozone (O3) and particulate matter (less than 10 micron) (PM10) in Peninsular Malaysia. Regression analysis was used to establish a statistical relationship between above mentioned concentrations recorded at 5 stations around Peninsular Malaysia and reflectance values from AVHRR data. Among the 5 constituents, PM10 showed a moderate correlation (R2) of 0.51 whilst, other constituents revealed poor correlation with correlation of less than 0.5. This model, was then applied to all the pixels in the image covering the whole Peninsular Malaysia. The obtained values are in Air Pollution Index/API values.